Transient Characteristics and Line Selection of Two-Point Grounding Faults on Same Phase in Resonant Grounding System - Yingtong LIU; Chun HUANG; Jingbo YUAN; Sen YAN (Zhongguo dianli)
Aiming at the low accuracy problem in line selection of two-point grounding faults on same phase in distribution network, a new fault feeder identification method suitable for two-point grounding faults on same phase in resonant grounding systems is proposed according to the transient characteristics of zero-sequence current (ZSC) and zero-sequence voltage (ZSV). Firstly, an equivalent zero-sequence network of two-point grounding fault is established and simplified, and the relationship between the ZSC transient of each line and the bus ZSV transient is derived, and the transient characteristics of two-point grounding faults on same phase are analyzed. And then, the fault transition resistance and zero-sequence distributed capacitance to ground of each line are obtained through fitting function, and a new fault line selection criterion is established based on the characteristic that the transition resistance of fault lines is far smaller than that of health lines, and the difference of transient characteristic quantities between zero-sequence current and capacitive current of each line. Finally, simulations are conducted on the two-point grounding faults on same phase under different working conditions, and the results show that the proposed method can accurately select two fault lines at the same time, and it is suitable for high impedance faults.